2016
DOI: 10.7717/peerj.2290
|View full text |Cite
|
Sign up to set email alerts
|

The physiological consequences of varied heat exposure events in adultMyzus persicae: a single prolonged exposure compared to repeated shorter exposures

Abstract: The study of environmental stress tolerance in aphids has primarily been at low temperatures. In these cases, and in the rare cases of high temperature tolerance assessments, all exposures had been during a single stress event. In the present study, we examined the physiological consequences of repeated high temperature exposure with recovery periods between these stress events in Myzus persicae. We subjected individuals to either a single prolonged three hour heating event, or three one hour heating events wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 86 publications
3
26
0
Order By: Relevance
“…Meteorological data indicate that the patterns of heat waves are changing, with increasing hot days and decreasing normal interval days in temperate regions that are concentrated in middle-latitudes. Heat waves inserted with short normal days may cause more severe biological impact, as they allow less time for systems to recover (Davis et al 2006, Mironidis and Savopoulou-Soultani 2008, Ghaedi and Andrew 2016. Our findings suggest that an increase in hot days and a decrease in normal days would inhibit the population increase of aphids through reducing survival, longevity and fecundity.…”
Section: Multiple Dimensions Of Heat Wavesmentioning
confidence: 85%
“…Meteorological data indicate that the patterns of heat waves are changing, with increasing hot days and decreasing normal interval days in temperate regions that are concentrated in middle-latitudes. Heat waves inserted with short normal days may cause more severe biological impact, as they allow less time for systems to recover (Davis et al 2006, Mironidis and Savopoulou-Soultani 2008, Ghaedi and Andrew 2016. Our findings suggest that an increase in hot days and a decrease in normal days would inhibit the population increase of aphids through reducing survival, longevity and fecundity.…”
Section: Multiple Dimensions Of Heat Wavesmentioning
confidence: 85%
“…These high survival rates may relate to recovery from heat injury during the cooler period between high temperatures or insufficient damage to affect survival 38 , which is common in insects 38 , 39 . It is believed that recovery times between high temperatures can allow injuries to be repaired, as aphids were shown to exhibit higher protein and osmolyte levels in a repeated exposure treatment compared to a prolonged exposure treatment group 39 . One possible explanation is that the proteins and osmolytes were upregulated during the recovery period 39 .…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that recovery times between high temperatures can allow injuries to be repaired, as aphids were shown to exhibit higher protein and osmolyte levels in a repeated exposure treatment compared to a prolonged exposure treatment group 39 . One possible explanation is that the proteins and osmolytes were upregulated during the recovery period 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Although a handful of studies have demonstrated that osmolytes accumulate under laboratory heat stress conditions in wheat, yeast and aphids (Li et al, 2009;Kumar et al, 2014;Wang et al, 2014;Ghaedi and Andrew, 2016), to our knowledge this is the first study showing that the content of an osmolyte molecule with known thermoprotective properties is dynamically regulated in response to thermal stress in nature. Individual thermal history was significantly and positively correlated with taurine content.…”
Section: Taurine As a Thermoprotective Osmolytementioning
confidence: 87%
“…Under heat stress conditions, the tissue contents of some osmolytes can increase (Li et al, 2009;Kumar et al, 2014;Wang et al, 2014;Ghaedi and Andrew, 2016), and these select osmolytes can act as thermoprotectants (Somero and Yancey, 1997;Yancey, 2005). Contents of organic osmolytes were determined from the mussels from the field sites.…”
Section: Gill Osmolyte Contentsmentioning
confidence: 99%